Pseudomyxoma peritonei: A Review (Faridpur Medical College Journal, 2013)
Pseudomyxoma peritonei (PMP) is rare clinical entity characterized by abundant extracellular mucinous material in the peritoneal cavity and tumoural implants on the peritoneal surfaces. The origin of PMP is controversial. It often arises from the goblet cells of large bowel or appendix. There is increase in MUC-2 secreting cells and accumulation of excessive mucin secreted by these cells in the peritoneal cavity. A ruptured appendiceal mucinous adenoma is the most common origin. Low grade ovarian malignancy is often associated. Patient may present with growing abdominal masses associated with abdominal pain, nausea, vomiting, fatigue and weight loss. Ultrasonogram and CT scan of the abdomen have role in diagnosis but diagnosis is often difficult before laparotomy or laparoscopy. Debulking surgery with intraperitoneal hyperthermic chemotherapy is the treatment. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13523 Faridpur Med. Coll. J. 2012;7(2):88-92